Aristocratic and Popular Piety in the Patronage of Music in the Fifteenth-century Netherlands - Bowers, Roger (Studies in church history, 1992)
It has always been recognized that during the fifteenth century the vigorous and affluent commercial towns of the Low Countries served as centres of artistic excellence, especially in respect of painting and of manuscript production and illumination. That the region was no less fertile a generator of practitioners and composers of music—especially of music for the Church—has also long been appreciated. If for present purposes the Low Countries be defined—rather generously, perhaps—as the region coterminous with the compact area covered by the six dioceses of Thérouanne, Arras, Cambrai, Tournai, Liège, and Utrecht (see map), then it was an area if not packed with great cathedrals, yet certainly thickly populated with great collegiate churches, which sustained skilled choirs and offered a good living and high esteem to musicians who composed; the area also sustained a catholic and generous patron and consumer of artistic enterprise of all sorts, sacred and secular music included, namely, the House of the Valois Dukes of Burgundy and its Habsburg successors. From the end of the fourteenth century to the first half of the sixteenth, the region produced church musicians in such numbers that it became the principal area of recruitment for those princes of the south of Europe who were seeking the ablest men available to staff their household chapels. The Avignon popes of the 1380s and 1390s, the dukes of Rimini and Savoy, and the Roman popes of the mid-fifteenth century, and from the 1470s onwards the fiercely competitive dukes of Milan and Ferrara, the popes, cardinals, and bishops of the Curia, the king of Naples, the prominent families and churches of Florence and Venice, all alike recruited from the North; and though many of the ablest, like Ciconia, Dufay, Josquin, Isaac, and Tinctoris, were lured south to spend their lives in the sunshine, many more remained at home to maintain the Low Countries tradition.